Empirical Evidence for Various Evolutionary Hypotheses on Species Demonstrating Increasing Mortality with Increasing Chronological Age in the Wild - Libertini, Giacinto (ScientificWorldJournal, 2008)
Many species show a significant increase in mortality with increasing chronological age in the wild. For this phenomenon, three possible general hypotheses are proposed, namely that: (1) it has no adaptive meaning; (2) it has an adaptive meaning; (3) the ancestry is the pivotal determinant. These hypotheses are evaluated according to their consistency with the empirical evidence. In particular, (1) the existence of many species with a constant, or almost constant, mortality rate, especially the so-called “animals with negligible senescence”; (2) the inverse correlation, observed in mammals and birds in the wild, between extrinsic mortality and the proportion of deaths due to intrinsic mortality; (3) the existence of highly sophisticated, genetically determined, and regulated mechanisms that limit and modulate cell duplication capacities and overall cell functionality. On the whole, the hypothesis of an adaptive meaning appears to be consistent with the empirical evidence, while the other two hypotheses hardly appear compatible.